If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5y + 5) = 5(2y + -5) Reorder the terms: 3(5 + 5y) = 5(2y + -5) (5 * 3 + 5y * 3) = 5(2y + -5) (15 + 15y) = 5(2y + -5) Reorder the terms: 15 + 15y = 5(-5 + 2y) 15 + 15y = (-5 * 5 + 2y * 5) 15 + 15y = (-25 + 10y) Solving 15 + 15y = -25 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. 15 + 15y + -10y = -25 + 10y + -10y Combine like terms: 15y + -10y = 5y 15 + 5y = -25 + 10y + -10y Combine like terms: 10y + -10y = 0 15 + 5y = -25 + 0 15 + 5y = -25 Add '-15' to each side of the equation. 15 + -15 + 5y = -25 + -15 Combine like terms: 15 + -15 = 0 0 + 5y = -25 + -15 5y = -25 + -15 Combine like terms: -25 + -15 = -40 5y = -40 Divide each side by '5'. y = -8 Simplifying y = -8
| 0=x^2+5x+12 | | 3[7-(n+5)]+19=5(3-n) | | y=-1/4+2 | | 22-5(4v-1)=-63 | | 2x+34-5x=1-8x+3 | | 17=1-3b-5b | | 6+(n-4)=2(2n+13) | | 3*x^2+2=50 | | 10h-8h=h+25 | | 18=-4x-2+4 | | 44=4(n+3)+4n | | 3y-20=30 | | 9x8/9 | | 23g=7.13 | | 3x+6=-18-3x | | 4-(p-1)+4p+7=p+4 | | 9+12x=-24+x | | 12x+17=13x+8 | | 2[t-(9-2t)]=4(2t-4) | | 6x+5y-1=10 | | 7x+1=-6+8x | | -24+x=x+13 | | 4x+12=36-6x | | 6(-s-6)-3(6s-3)=s+8+3s | | 193=41*1+0.40x | | -1.4+(-5.7)= | | 6t-24=0 | | X+76+110=180 | | 8x+9(.25x)=10 | | -2+26x=25x | | 4*8.4+8*0.8=40 | | -3-s=4tj+19 |